The daily rhythm of milk synthesis is dependent on the timing of feed intake in dairy cows. Issue 6 (24th June 2014) - Rottman, L. Whitney; Ying, Yun; Zhou, Kan; Bartell, Paul A.; Harvatine, Kevin J.
Abstract Regulation of the daily rhythm of milk synthesis is important to production animals and breastfeeding, but is difficult to observe in nursing animals. The rate of food intake varies over the day and is expected to create a daily rhythm of nutrient absorption. The objective of this study was to determine if the timing of food intake entrains a daily pattern of milk synthesis. Seventeen Holstein cows were used in a crossover design. Treatments were ad libitum feeding of a total mixed ration once daily (1× fed) or fed in four equal meals every 6 h (4× fed). Cows were milked every 6 h the last 7 days of each period. There was a treatment by time of day interaction for milk and milk component yield and concentration. Milk fat and protein concentration and yield exhibited a daily rhythm and the amplitude of the rhythm was reduced in 4× fed. In addition, milk fat percent was higher in 4× fed than 1× fed at three of the four milking intervals (0.22–0.45% higher) and 4× fed increased daily milk fat yield. Treatment by time of day interactions were detected for plasma glucose, insulin, and blood urea nitrogen. These variables also fit a cosine function with a 24 h period and the amplitudes of plasma glucose, insulin, and blood urea nitrogen rhythms were decreased by 4× feeding. In conclusion, there is a circadian pattern of milk synthesis in the dairy cow that is responsive to the timing of food intake.